Method for the earlier recognition of abnormal stature. Issue 7 (July 1983) - Green, A A; MacFarlane, J A
Abstract : Two hundred and twenty seven children with a height below the 3rd or above the 97th centile were seen consecutively in the Oxford growth clinic. Their referral ages were analysed to determine the pattern of referral. Eighty seven per cent of the children had short stature. In 40% of these there was an organic reason for abnormal growth–the most common conditions being growth hormone deficiency, hypothyroidism, and Turner's syndrome–but the rest had genetic short stature or 'constitutional' delay in puberty. Many children who could have been treated effectively were referred too late, for effective treatment to ensure normal adult height because of this we have developed full sized percentile charts to screen populations of children so that abnormal stature can be recognised immediately.